The effect of rebound exercise on cognition and balance of females with overweight and obesity - Chidiebele Petronilla Ojukwu; Izuchukwu Simeon Nnyaba; Stephen Sunday Ede; Adaora Justina Okemuo; Judith Amaka Enebe (Libyan Journal of Medicine)
Balance issues have been reported to be common among females with overweight or obesity with associated fall risks. Despite the increasing reports of the negative impacts of obesity on balance and cognition, there is a scarcity of research aimed at evaluating effective interventions. To examine the effects of rebound exercises on cognition and balance among females with overweight and obesity. This Quasi-experimental study used the purposive sampling method to recruit 20 female students (aged 17–35 years) with overweight and obese at the Evangel University Akaeze, Ebonyi State Nigeria. Rebound exercise intervention was administered to all participants at the gym for 30 minutes in each session, three times a week for six weeks, while their cognitive performances, stationary balance, and dynamic balance were measured pre-and post-trial using Trail Marking Test Apparatuses, Unilateral Pedal Tests, and Meter Backward Walk Test respectively. There was a significant (p < 0.001) difference in the participants’ cognition values across weeks 1, 3, and 6 with a progressive improvement over time. There was also a significant (p < 0.05) difference in the participants’ static and dynamic balance values across weeks 1, 3, and 6 with a progressive improvement in balance performance over time. Rebound exercise significantly improved the cognition and balance of females with overweight or obese. This finding suggests a promising intervention to improve balance and cognitive-related problems in this population. Registered retrospectively in the Pan African Clinical Trial Registry, identification number for the registry is PACTR202405746557031. Dated 2 May 2024.